Morphological, structural, thermal and optical properties of Zn/Mg-doped TiO2 nanostructures for optoelectronic applications. (February 2022) - Javed, Hafiz Muhammad Asif; Adnan, Muhammad; Qureshi, Akbar Ali; Javed, Sofia; Adeel, Muhammad; Akram, Muhammad Aftab; Shahid, M.; Irfan Ahmad, M.; Afzaal, M.; Abd-Rabboh, Hisham S.M.; Arif, M.
Highlights: Zn and Mg doped TiO2 nanostructures were prepared via facile Sol-Gel technique. ZnO-doped TiO2 nanoparticles demonstrated excellent thermal stability with less surface defects. Mg-doped TiO2 nanoparticles exhibited remarkable absorption in visible region by suppressing recombination reactions. The obtained results from PL measurements indicate Zn/Mg-doped TiO2 nanostructures could be used as potential candidate in optoelectronic applications. Abstract: The advanced research of new optoelectronic materials opens avenues for improved energy devices. In the present research, the facile synthesis of TiO2 nanoparticles and ZnO/Mg-doped TiO2 nanoparticles were carried out by sol–gel technique. The synthesized samples were characterized for morphological, structural, optical, and thermal properties. Scanning Electron Microscope (SEM) indicated that a distinct increase in the size of TiO2 nanoparticles due to ZnO/Mg-doping in the form of clusters. The crystalline nature of anatase TiO2 and doping of Mg and ZnO is corroborated by XRD patterns and Raman data. Moreover, ZnO and Mg doping affirm a clear shift in energy gap values confirmed by UV–Vis spectroscopic analysis and the surface plasmonic effects observed by photoluminescence analysis. TGA analysis indicates the remarkable results on the thermal stability of newly synthesized samples. It shows the maximum weight retention in the case of ZnO doped TiO2 nanostructures. Thus, these optimized materials can be recommended for future optoelectronic devices.